Impact of Dried Thyme Leaf Meal on Production Performance, Egg Quality and Blood Parameters of Laying Hens - Yasin, Abdulwahid; Tamiru, Metekia; Alkhtib, Ashraf; Mohammed, Abdo; Tadesse, Tagesse; Wamatu, Jane; Burton, Emily (Wiley Open Access, 2025)
Background The use of commercially extracted phytogenic compounds to maintain poultry health and productivity in the absence of in-feed antibiotics is prohibitively costly in developing countries.